FINANCIAL STATEMENT FRAUD: PENGUJIAN FRAUD HEXAGON DENGAN MODERASI AUDIT COMMITTEE - Fanny Oktaviany; Reskino (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
Financial statement fraud has received a lot of attention over the past few years and will continue to become a concern because financial statement fraud can appear in various forms such as hiding assets, exaggerating assets, sales and profits, understating liabilities and costs. Even once deceptive fraudulent accounting practices are initiated, a whole system of manipulation will be used to maintain the appearance of sustainability. Financial reports are used by shareholders to measure company performance versus expectations. However, sometimes manipulated to fulfill one's greed. Many studies have been conducted in detecting and predicting the occurrence of financial statement fraud. This study explores the significant impact on corporate culture in the occurrence of financial statement fraud. Culture has been widely accepted as behavior pattern that influences society's character. In studying the occurrence of financial statement fraud, elements of corporate culture need to be considered along with other factors. This research provides a holistic view of the concept of culture and its influence on organizations and behavior. The second objective is to discuss the influence of corporate culture from the perspective of financial statement fraud. The research findings provide suggestions for improving corporate culture.